In the light of the aurora : Optical auroral research in northernmost Europe (Copenhagen : Nordic Council of Ministers, 2009)
The aurora, or northern lights, is the most variable light phenomenon in the sky and the result of physical processes taking place in near-Earth space. The colours, shapes, intensities, locations and movements of auroral forms give us information about these processes. Ground-based optical studies are superior for high-resolution measurements and to distinguish temporal and spatial effects. Arctic Europe is a most convenient place to study the aurora. Many instruments and research facilities have been placed here. The Network for Groundbased Optical Auroral Research in the Arctic Region is supported by the Nordic Council of Ministers and consists of all research institutions in northern Norway, Sweden, Finland and on theKola Peninsula active in optical auroral research. This reportintroduces optical aurora and optical research methods, research institutions and research infrastructure. It also describes the activities of the network: workshops, mobility programme and scientific results.